Comparative Analysis of Controller Area Network’s Migration Code in a “Shared-Clock” Environment: Migration Code Metric Analysis - Amir, Muhammad; Shah, Syed Waqar; Rehman, Bilal ur; Pont, Michael J. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Industrial and automotive applications since long have been utilizing the Controller Area Network (CAN) protocol for their communications needs. History relating to the use of CAN suggests that although it is cost-effective and less complex; a lack of flexibility and an incomprehensive fault-management strategy makes its use scarce in safety-critical applications. This scarcity of CAN in safety related applications is primarily due the fact that this protocol was originally implemented using a bus-topology. Previously, through our research, a migration of CAN from bus to star topology was suggested. The results of which exhibited that such a migration positively impacted the flexibility and fault-management capability of CAN. Here, in this paper, a comparative analysis of the codes used for both CAN architectures (bus and star) is presented. The analysis exhibits that such a fruitful migration can be achieved through almost the same software-overhead and complexity as was in the original CANbus-based architecture.